2019
DOI: 10.1088/1361-665x/ab083c
|View full text |Cite
|
Sign up to set email alerts
|

A piezo-metastructure with bistable circuit shunts for adaptive nonreciprocal wave transmission

Abstract: In this paper, we present a piezo-metastructure shunted with bistable circuits to achieve adaptive nonreciprocal elastic wave transmission. Static properties of the bistable circuit are first investigated, followed by numerical investigation of wave transmission characteristics on the nonlinear piezo-metastructure. Both the local-resonance bandgap and the bandgap transmission phenomenon, also known as supratransmission, are explored and investigated. By introducing circuit asymmetry, the supratransmission thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 40 publications
0
12
0
4
Order By: Relevance
“…The substrate layer has thickness h s , density ρ s , elastic modulus E s , and Poisson's ratio ] s while the piezoelectric layers have thickness h p and density ρ p . The piezoelectric elements are connected to external circuitry through conductive circular electrodes (red and blue in Figure 1) with radius r p and a thickness that is assumed to be negligible (Zheng et al, 2019). The electrodes are arranged in a honeycomb lattice formation that contains the symmetries required to achieve the elastic analog of the QVHE.…”
Section: System Descriptionmentioning
confidence: 99%
“…The substrate layer has thickness h s , density ρ s , elastic modulus E s , and Poisson's ratio ] s while the piezoelectric layers have thickness h p and density ρ p . The piezoelectric elements are connected to external circuitry through conductive circular electrodes (red and blue in Figure 1) with radius r p and a thickness that is assumed to be negligible (Zheng et al, 2019). The electrodes are arranged in a honeycomb lattice formation that contains the symmetries required to achieve the elastic analog of the QVHE.…”
Section: System Descriptionmentioning
confidence: 99%
“…Multistable structures comprising arrays of interconnected bistable elements have recently emerged as a powerful platform to manipulate and control the propagation of mechanical signals, owing to their ability to support the propagation of transition waves-nonlinear waves similar to those of falling dominoes that sequentially switch all elements 15 . Such transition waves have been recently exploited to enable unidirectional propagation [16][17][18] , achieve complex shape reconfigurations 19 and realize structures that can be quickly deployed 20 , as well as mechanical logic gates 21 . However, almost all previous studies have focused on bistable elements that possess two energy minima of different height [16][17][18][19][20][21] and, therefore, support unidirectional wave propagation.…”
mentioning
confidence: 99%
“…Such transition waves have been recently exploited to enable unidirectional propagation [16][17][18] , achieve complex shape reconfigurations 19 and realize structures that can be quickly deployed 20 , as well as mechanical logic gates 21 . However, almost all previous studies have focused on bistable elements that possess two energy minima of different height [16][17][18][19][20][21] and, therefore, support unidirectional wave propagation. By contrast, the advantages and challenges associated with the propagation of transition waves in systems whose constituents possess equal energy minima have received very limited attention 22 .…”
mentioning
confidence: 99%
“…If such energy is transmitted to the neighboring elements through (elastic) connections, waves similar to those of a falling dominoes (11) are initiated that switch sequentially all building blocks. It has been recently shown that such transition waves offer new opportunities to manipulate the propagation of mechanical signals and enable unidirectional propagation (8,12,13) and energy harvesting (14,15) as well as simple mechanical logic (9); here, we will investigate their use to realize foldable structures that can be quickly deployed and automatically lock in place.…”
mentioning
confidence: 99%